Hibridismo musical e religiosidade popular: DJ tudo e sua gente de todo lugar - Silva, Anatote Lopes da (2018)
The Brazilian context is characterized by an ethnic diversity that contributes to racial, ideological, religious and sociocultural pluralism and in this plural and secular environment the diversity of the new and the modern, and the old and the traditional, live together. This research investigates an experience of religious renewal in the umbandist religion. The result of the synthesis of the old and the new, the reinsertion of postmodern artistic production in the brazilian cultural environment, specifically in the religion of African matrix, where popular traditions and the sophistication of the old religious traditions are recorded. The author discusses the fundamental link in the structure of the myths of the religions that make up the inner diversity of the Umbanda, general aspects of the history of ethnic identity, formation and the African pantheon and its influences in the Brazilian religious field. And, finally, the development and observed contribution of the object of the case study confirms the use of new modern technologies and new media, contributing to the preservation of the Afro-Brazilian musical tradition.